Image quality of coronary CT angiography (CCTA) using 640-slice scanner: qualitative and quantitative assessments of coronary arteries visibility - Shahril Shamsul,; Akmal Sabarudin,; Hamzaini Abdul Hamid,; Norzailin Abu Bakar,; Oteh Maskon,; Muhammad Khalis Abdul Karim, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The purpose of this study was to evaluate the image quality and diagnostic accuracy of coronary computed tomography angiography (CCTA) using 640-slice scanner. Advancement of multidetector computed tomography (MDCT) technology with higher spatial, temporal resolution, and increasing detector array have improved the image quality and diagnostic accuracy of CCTA. A total of 25 patients (12 men and 13 women) underwent CCTA was chosen and data was acquired by 640-slice scanner. All 16 segments of coronary arteries were evaluated by two reviewers using a 4-likert scale for qualitative assessment. In quantitative assessment, the evaluation of 4 main coronary arteries were analysed in terms of signal intensity (SI), image noise, signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR). All 25 patients with a mean age of 52.88 ± 14.75 years old and body mass index (BMI) of 24.24 ± 3.28 kg/m2 were analysed. In qualitative assessment, from the total of 400 segments, 379 segments (95 %) have diagnostic value while 21 segments do not have diagnostic value, which means 5 % artefact was detected. In quantitative assessment, there was no statistical differences in gender, race, and BMI (p>0.05). Overall evaluation showed that higher SI at the left main artery (LM) at 393.7 ± 47.19. Image noise was higher at right coronary artery (RCA) at 39.01 ± 13.97. SNR and CNR showed higher at left anterior descending (LAD) with 12.73 ± 5.17 and LM 9.14 ± 4.2, respectively. In conclusion, this study indicates that 640-slice MDCT has higher diagnostic value in CCTA examination with 95 % vessel visibility with 5 % artefact detection.